A Narrative Review of Pheochromocytoma in VHL (Journal of Kidney Cancer, 2024)
This systematic review aims to investigate the clinical presentation, diagnostic methods, and management strategies for pheochromocytoma in patients with von Hippel-Lindau (VHL) disease, an autosomal dominant disorder that predisposes individuals to the development of various tumors, including pheochromocytomas. Pheochromocytoma is a rare neuroendocrine tumor of the adrenal medulla that occurs sporadically or as part of an inherited syndrome. The incidence of pheochromocytoma in VHL patients is estimated to be between 10–20%, making it the second most common tumor associated with VHL. Early detection and management of pheochromocytoma in VHL patients are critical for patient outcomes, as these tumors can cause severe hypertension, cardiovascular complications, and death. This review highlights the importance of screening for pheochromocytoma in VHL patients and discusses the current diagnostic and management strategies to optimize patient care.